Post-mortem Findings in Huntington's Deep Brain Stimulation: A Moving Target Due to Atrophy. (27th April 2016) - Vedam-Mai, Vinata; Martinez-Ramirez, Daniel; Hilliard, Justin D.; Carbunaru, Samuel; Yachnis, Anthony T.; Bloom, Joshua; Keeling, Peyton; Awe, Lisa; Foote, Kelly D.; Okun, Michael S.
Background: Deep brain stimulation (DBS) has been shown to be effective for Parkinson's disease, essential tremor, and primary dystonia. However, mixed results have been reported in Huntington's disease (HD). Case Report: A single case of HD DBS was identified from the University of Florida DBS Brain Tissue Network. The clinical presentation, evolution, surgical planning, DBS parameters, clinical outcomes, and brain pathological changes are summarized. Discussion: This case of HD DBS revealed that chorea may improve and be sustained. Minimal histopathological changes were noted around the DBS leads. Severe atrophy due to HD likely changed the DBS lead position relative to the internal capsule.